The Impact of Comorbidities On Pain Severity in Patients With Low Back Pain: A Cross-Sectional Study - Tarigan, Abul A'la; Tiara, Anita; Pane, Mustika Dewi (Yayasan Sagita Akademia Maju, 2024)
The quality of life for people who suffer from low back pain (LBP) is significantly reduced, making it a major worldwide health concern. Patients with LBP frequently have comorbid diseases like hypertension and hyperlipidemia, which can exacerbate pain and make therapy more difficult. The purpose of this study is to examine the connection between comorbidities and the incidence of LBP in patients who visit the RSUDZA Banda Aceh Neurology Outpatient Clinic. In this study, 237 LBP patients from the Neurology Outpatient Clinic at RSUDZA were selected using a cross-sectional methodology between 12 April to May 2023. A sociodemographic questionnaire and the Modified Self-Administered Comorbidity Questionnaire (MSACQ) were used to gather data. The association between comorbidities and the incidence of LBP was examined using the chi-square test. The most prevalent comorbid conditions among the 237 responders were hypertension and hyperlipidemia, with 161 people (67.9%) having comorbidities. Mild pain was experienced by 87.8% of patients. Comorbid conditions had a substantial impact on the severity of pain in patients with LBP, according to the chi-square test, which revealed a strong correlation between comorbidities and the occurrence of LBP (p-value = 0.000). This study suggests a strong correlation between comorbidities and LBP incidence. In relation to LBP, hypertension and hyperlipidemia are the most prevalent comorbidities. To enhance treatment results and patients' quality of life, a comprehensive strategy to managing LBP is required, taking into account both the pain and any concomitant conditions.